2014
DOI: 10.1136/bmjopen-2014-005175
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a prospective, multicentre registry study of stenting for symptomatic intracranial artery stenosis in China

Abstract: IntroductionThe SAMMPRIS trial suggested that aggressive treatment was superior to endovascular stenting in patients with severe symptomatic intracranial atherosclerotic stenosis (ICAS) due to high complication rates in patients in the stenting group. Given that 12.2% patients failed aggressive medical therapy in the SAMMPRIS study, it is imperative to perform a multicentre prospective registry study of stenting for patients with ICAS in China. This study aims to evaluate the safety and efficacy of endovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…18 This study was a prospective single-arm registry study with 20 participating sites. Approval by each site's institutional review board or ethics committee was obtained.…”
Section: Overall Designmentioning
confidence: 99%
“…18 This study was a prospective single-arm registry study with 20 participating sites. Approval by each site's institutional review board or ethics committee was obtained.…”
Section: Overall Designmentioning
confidence: 99%
“…In the VISSIT (the Vitesse Intracranial Stent Study for Ischemic Stroke Therapy) trial, worse outcomes after stenting were also shown with a different (i.e., balloon expanding) stent in comparison with medical therapy in symptomatic intracranial atherosclerotic stenosis (24% vs. 9% at 30 days, 36% vs. 15% at 12 months follow‐up) (Compter et al., ; Derdeyn et al., ; Zaidat et al., ). Despite the disappointing performance of intracranial stenting in both VISSIT and SAMMPRIS, it is possible that improvement of operator experience and periprocedural factors such as blood pressure management may lead to improved outcomes after stenting in future trials (Wang et al., ; Zaidat et al., ). Newer stent technology could possibly also enhance the safety and success of future endovascular procedures (Zaidat et al., ).…”
Section: Treatment Of Intracranial Atherosclerotic Stenosismentioning
confidence: 99%
“…Newer stent technology could possibly also enhance the safety and success of future endovascular procedures (Zaidat et al., ). Device selection based on arterial access and lesion morphology is currently implemented in a large Chinese study (Wang et al., ), in which self‐expanding stents are preferably used in patients with tortuous arterial access, while balloon‐expandable stents are preferred in patients with smoother access.…”
Section: Treatment Of Intracranial Atherosclerotic Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…15 16 The first one was a single-centre randomised trial, the results of which demonstrated that PTAS is as effective as medical treatment 16. The result of the second study, a multicentre registry study, showed that the incidence of stroke, transient ischaemic attack (TIA) and death in 30 days after stenting was 4.3%, which is lower than the incidence in the SAMMPRIS trial 17.…”
Section: Introductionmentioning
confidence: 99%